23rd. European Conference on Biomaterials Tampere, Finland 11 - 15 September 2010 - Sam'an Malik, Masudi (Pusat Pengajian Sains Perubatan, 2010)
Calcium phosphate ceramics have gained wide-spread attention due to their compositional and structural similarity to the mineralized constituent in hard tissues. Hydroxyapatite is the main mineral constituent of natural bone, and thus synthetic calcium phosphate ceramics may create an excellent bond with natural tissue and can even stimulate new bone growth. Biphasic Calcium Phosphate (BCP) is a mixture of HA and [3-TCP that has been used extensively for dental applications and bone grafts. BCP is bioactive and bioresorbable materials that can be controlled by manipulating the HA to [3-TCP ratio. Another advantage of BCP is the strong dire.ct bonding with host bone. However, due to their relatively low strength and toughness, susceptibility to physiological attack and poor fatigue properties, the biomedical uses ofBCP are limited to non-load bearing applications. One of the most promising approaches to increase the strength in ceramics is through transformation toughening based on the tetragonal-monoclinic transformation of Zirconia (Zr). A ceramic with dispersed tetragonal Zr in the form of Zr02 can be used to produce a biocomposite Zr and calcium phosphate biomaterial for better strength, x-ray contrast and opaqueness. To this aims, we carried out a chemical and structural analysis of Zr-doped BCP.